Endoventricular Deep Brain Stimulation of the Third Ventricle: Proof of Concept and Application to Cluster Headache. Issue 6 (December 2016) - Chabardès, Stéphan; Carron, Romain; Seigneuret, Eric; Torres, Napoleon; Goetz, Laurent; Krainik, Alexandre; Piallat, Brigitte; Pham, Pascale; David, Olivier; Giraud, Pierrick; Benabid, Alim Louis
Abstract : BACKGROUND: The third ventricle (3rd V) is surrounded by centers related to satiety, homeostasis, hormones, sleep, memory, and pain. Stimulation of the wall of the 3rd V could be useful to treat disorders related to dysfunction of the hypothalamus. OBJECTIVE: To assess safety and efficacy of endoventricular electrical stimulation of the hypothalamus using a floating deep brain stimulation (DBS) lead laid on the floor of the 3rd V to treat refractory cluster headaches (CH). METHODS: Seven patients, aged 24 to 60 years, experiencing chronic CH (mean chronic duration 5.8 ± 2.5 years) were enrolled in this pilot, prospective, open study assessing the safety and potential efficacy of chronic DBS of the 3rd V. Number of attacks was collected during baseline and was compared with those occurring at 3, 6, and 12 months postoperation. Any side effects that occurred during or after surgery were reported. Effect on mood was assessed using the Hospital Anxiety and Depression scale during baseline and at 6 and 12 months postoperation. RESULTS: Insertion of the lead into the posterior 3rd V and chronic stimulation was feasible and safe in all patients. The voltage ranged from 0.9 to 2.3 volts. The most common side effect was transient trembling vision during stimulation. At 12 months, 3 of 7 patients were pain free, 2 had 90% improvement, 1 of 7 had 75% improvement, and 1 of 7 was not significantly improved. CONCLUSION: This proof of concept demonstrates the feasibility, safety, and potential efficacy of 3rd V DBS using an endoventricular road that could be applied to treat various diseases involving hypothalamic areas. ABBREVIATIONS: CCH, chronic cluster headache CH, cluster headache DBS, deep brain stimulation HAD, hospital anxiety depression ONS, occipital nerve stimulation PAG, periaqueductal gray matter PH, posterior hypothalamus PVG, periventricular gray matter 3rd V, third ventricle Abstract : Supplemental Digital Content is Available in the Text.